Cross-cultural investigation of COVID-19 related acute stress: A network analysis. (November 2021) - Tsur, Noga; Bachem, Rahel; Zhou, Xiao; Levin, Yafit; Abu-Raiya, Hisham; Maercker, Andreas
Abstract: The outbreak of the COVID-19 pandemic has confronted humanity with an ongoing biopsychosocial stressor, imposing multifaceted challenges to individuals and societies. Particularly, the pandemic reflects an ongoing, potentially life-threatening danger to self and others, which may instigate acute stress symptoms (ASS). This study utilized a network framework to assess cross-national ASS a short time following the initial COVID-19 outbreak. Three samples of adult participants from China, Israel, and Switzerland completed a self-report assessment of acute stress symptoms. Network analyses were utilized to uncover the phenotype and dynamics of different ASS in these three countries. The ASS network analyses revealed extensive connections in all networks and reflected the structure of ASS. The centrality indexes in all networks were from the hyperarousal cluster. "Feeling jumpy" was the node with the highest strength centrality in the Israeli sample and "physiological reactivity" was the item with the highest centrality in the Swiss sample. In the Chinese sample, the item with the highest centrality was "feeling alert to danger." The findings reveal that despite some variations, the overall clinical picture of ASS in response to the COVID-19 pandemic is universal. These findings highlight the centrality of hyperarousal symptoms, presumably reflecting its significance for clinical interventions. Highlights: Acute stress symptoms (ASS) in response to COVID-19 were tested in Israel, Switzerland and China. Network analysis conveyed similar patterns of associations between ASS in all three countries. Hyperarousal symptoms emerged as a central symptom in the ASS network. Hyperarousal may be important to target in early interventions for ASS due to COVID-19.